The Lilac-tailed Parrotlet (Touit batavica), a new record for Colombia - Ahumada Jorge A.; Vander der Wolf Peter A. J.; Troncoso P. Francisco (Caldasia)
The Lilac-tailed Parrotlet has been reported in Surinam, Guyana and Venezuela and on the islands of Trinidad and Tobago. In northern Venezuela (north of the Orinoco river) the species occurs from Sucre west to Merida, and South of the Orinoco east to Bolívar (Meyer de Schauensee & Phleps, 1978). This parrot is relatively abundant in lowland forests and valleys but can extend from dry deciduous forest up to 1700 m in mountain forests. The birds are usually gregarious and have been reported in groups up to thirty or more (Forshaw, 1978). In this paper, we report the firstrecord of Touit batavica for Colombia.